The self-concept of senior students of Altavas National School in relation to academic achievement - Patnugot, Linavilla Y. 1955-
The focus of the study is to determine the nature of the relationship that exists between self-concept and academic achievement. It sought to find out whether there is a positive significant relationship between self-concept and academic achievement. Further, it investigated the effect of showing class grades on the self-concept of the students.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Self-perception.; Academic achievement